Alkalinization Of The Gastroesophageal Region And Blood Coagulation Abilities Of Oyster Mushroom (Pleurotus Ostreatus) - Miguel, Menard; Bantique, Mark Anthony; Laman, Jane; Sangil, Cherry Mae (Southeast Asian Journal of Science and Technology, 2019)
Improper intake of food that people eat can cause a lot of diseases. Too much intake of food high in acid may affect the condition of the stomach and may lead to Gastroesophageal Reflux Disease or Acid Reflux Disease. Apart from it, there are also diseases that a lot of people endure in relation to their blood clotting. Oyster mushroom (Pleurotus ostreatus)is known for the presence of numerous nutritional compositions and various active ingredients, and it have been reported to have antidiabetic, antibacterial, anticholestrolic, antiarthritic, antioxidant, anticancer, eye health and antiviral activities (Deepalakshmi, et.al, 2013).This study aimed to find out the alkalinization of the gastroesophageal region and blood coagulation abilities of oyster mushroom (Pleurotus ostreatus).Thus, this study undergone salivary and blood coagulation tests, and the researchers utilized ANOVA and t-test to determine the significant differences among the treatment groups. Based on the results obtained from the entire experiments, it was found out that Pleurotus ostreatus can: increase the pH level of gastroesophageal region, decrease the blood bleeding time, and accelerate the blood clotting time.